2020
DOI: 10.1039/c9an01926j
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of activation processes for 3D printed PLA-graphene electrodes: electrochemical properties and application for sensing of dopamine

Abstract: This paper reports the comparison of the electrochemical properties of 3D PLA-graphene electrodes (PLA-G) under different activation conditions and through different processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(89 citation statements)
references
References 57 publications
10
79
0
Order By: Relevance
“…Such dual activation treatments have demonstrated to improve even more the electrochemical response of 3D-printed BM devices, resulting in composite electrodes with characteristics similar to functionalized graphene surfaces. [37,50,51]…”
Section: Surface Activationmentioning
confidence: 99%
“…Such dual activation treatments have demonstrated to improve even more the electrochemical response of 3D-printed BM devices, resulting in composite electrodes with characteristics similar to functionalized graphene surfaces. [37,50,51]…”
Section: Surface Activationmentioning
confidence: 99%
“…Thus organic solvents are generally used to remove or reduce the potential protective layer created by PLA when utilized together with a conductive material, in order to achieve electrodes with a better conductivity (dos Santos et al, 2019 ; Gusmão et al, 2019 ; Richter et al, 2019 ; Wirth et al, 2019 ). In this context, the work of Kalinke et al ( 2020 ) showed a considerable improvement of the electrochemical properties of a 3D-printed electrode made of G-PLA when the graphene nanoribbon structures were exposed through the reduction of the protective layer of PLA, accomplished by solvents or saponification (Kalinke et al, 2020 ). An electrochemical characterization of such device was performed by cyclic voltammetry (CV).…”
Section: Novel Materials For Printingmentioning
confidence: 99%
“…The materials used are often filaments of polymers, metals, composites, and ceramics that get extruded through a heated nozzle. Composites of thermoplastics and carbon-based materials (i.e., graphene, graphite, carbon black, carbon nanotubes) are used as conductive materials together with the insulating nature of thermoplastics filaments (e.g., acrylonitrile butadiene styrene, ABS) (Wei et al, 2015 ; Katic et al, 2019 ; Foster et al, 2020 ; Kalinke et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing, also known as 3D printing, is making rapid inroads in manufacturing, and advanced fabrications that are quickly moving into production [23]. 3D printing has been utilized in development and fabrication of sensors for detection of glucose [24], drugs [25], trace elements [26], neurotransmitters [27], nucleic acids [28], and proteins [29]. The vast scope and innovative nature of 3D printing in development of biosensors is backed by the versatility of options provided by the immense progress in the design and production of desktop 3D printers.…”
Section: Introductionmentioning
confidence: 99%